Health-Related Anxiety in the Management of Oral Soreness in an HIVSeropositive Patient - Mandasari, Masita; Syarif, Zulvia Oktanida; Rahmayanti, Febrina (UI Scholars Hub, 2020)
The number of people living with HIV (PLHIV) has been increasing since the first known case in the early 1980s. However, PLHIV can also experience comorbidities, such as health anxiety. In the oral cavity, anxiety is often associated with the etiology of parafunctional habits. Anxiety can be measured using self-administered instruments, such as the Hospital Anxiety and Depression Scale (HADS) and Short-Health Anxiety Inventory (SHAI), which is specifically used in the medical setting. Objectives: We are describing a case of HIV positive patient with health anxiety who presented to the oral medicine clinic in our hospital with a complaint of discomfort on his lateral sides of the tongue. Case Report: A 35-year-old male patient came to the oral medicine clinic complaining of discomfort on his tongue, which presented for one week. The patient was alarmed by two bumps seen on the right lateral side of his tongue and soreness on the left lateral side. Nystatin oral suspension was prescribed by a medical doctor but discontinued by the patient. The patient was positive for HIV and took ART routinely. Extraoral and intraoral examinations showed unremarkable findings except slightly enlarged and erythematous foliate papillae on the left lateral side of the tongue. The patient was prescribed an antiseptic mouth rinse. After several days, his symptoms had dissipated. Since the patient reported anxiety regarding his health and HIV status, we asked the patient to complete the HADS and SHAI self-assessment tools to measure his level of anxiety. The patient was shown to have anxiety using the SHAI (total score = 21). Conclusion: Health anxiety is a condition that an individual misinterprets as a benign bodily sensation. The management of this type of patient involves addressing the local predisposing factor of the oral complaint and maintaining oral hygiene, followed by an evaluation of health anxiety for the basis of referral to a psychological expert.